Дослідження реакції рослин пшениці м’якої з транслокацією 1BL/1RS на гамма-опромінення - Созінов, І.О.; Козуб, Н.О.; Бідник, Г.Я.; Дем’янова, Н.О.; Карелов, А.В.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2015)
Aims. The 1BL/1RS translocation is the most widespread introgression among common wheat cultivars. To reveal regularities of the response of plants to gamma-irradiation of dry seeds depending on the presence of 1BL/1RS, further investigation of survival rate and productivity traits was carried out. Methods. Dry F2 seeds from crossing Bezostaya 1 lines were treated with gamma-radiation at 200 Gy. Each F2 plant was characterized with respect to yield traits. The presence of 1BL/1RS was analyzed by electrophoresis of gliadins. Results. No differences in the survival rate depending on the presence of 1BL/1RS were revealed. At gamma irradiation, the homozygote for 1BL/1RS showed the smallest reduction in plant productivity traits, which is in agreement with the previous results. Conclusions. The results provide further support for lower sensitivity (with respect to productivity traits) of genotypes with the 1BL/1RS translocation to gamma-irradiation of dry seeds. Keywords: Triticum aestivum L., 1BL/1RS translocation, gamma-irradiation, productivity.